2018
DOI: 10.1007/s00420-018-1356-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between hyperacusis and psychosocial work factors in the general population

Abstract: The results suggest that worrying about aspects at work, perceiving low social support, and not perceiving being rewarded at work are associated with hyperacusis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Meanwhile, Halevi-Katz (37) further classified responses into five grades: never, seldom, sometimes, often, or always. There were 8 other studies that were diagnosed by asking questions (4,6,7,19,23,25,34,37). Only two studies used the same questions for diagnosis (4,6).…”
Section: Diagnosis and Evaluationmentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, Halevi-Katz (37) further classified responses into five grades: never, seldom, sometimes, often, or always. There were 8 other studies that were diagnosed by asking questions (4,6,7,19,23,25,34,37). Only two studies used the same questions for diagnosis (4,6).…”
Section: Diagnosis and Evaluationmentioning
confidence: 99%
“…There were 8 other studies that were diagnosed by asking questions (4,6,7,19,23,25,34,37). Only two studies used the same questions for diagnosis (4,6). The discomfort thresholds (LDL, UCL, intolerance sound level, etc) had been measured in 9 studies (2, 9, 20, 22, 24, 25, 27, 28, 33), of which 6 used lowered discomfort loudness as the diagnostic criteria (2,9,15,20,22,28).…”
Section: Diagnosis and Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…This would suggest that the majority of recently published research in hyperacusis has not necessarily been addressing the areas of concern. A search of Google Scholar revealed that the most recent publications for hyperacusis have focused on basic research questions around causes of hyperacusis,32–34 or on research investigating hyperacusis and the workplace 35. The only relevant ongoing trial is investigating ‘Exposure Therapy for Auditory Sensitivity in Autism’ (ClinicalTrials.gov Identifier: NCT03206996).…”
Section: Discussionmentioning
confidence: 99%